Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1997
DOI: 10.3109/15563659709001189
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Adult Poisoning at China Medical University

Abstract: This first epidemiological report of adult poisoning from the People's Republic of China offers emergency physicians and toxicologists a preliminary understanding of the most common toxicologic problems seen in adults in a university hospital in China, and will aid in improving the delivery of emergency care to poisoned patients in the People's Republic of China.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
1
5

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 1 publication
2
11
1
5
Order By: Relevance
“…Acil servise başvuruda zehirlenme olguları Çin'de %3, İngiltere'de %1 oranında bulunmuştur. 11,12 Türkiye'de ise bu oran %0,5-1,57 olarak bildirilmiştir. 13 Ülkemizde yapılan diğer çalışmalarda ise en düşük %0,72 oranında İç Anadolu Bölgesi'nde, en yüksek %2,97 oranında Karadeniz Bölgesi'nde tespit edilmiştir.…”
Section: Gereç Ve Yöntemunclassified
See 1 more Smart Citation
“…Acil servise başvuruda zehirlenme olguları Çin'de %3, İngiltere'de %1 oranında bulunmuştur. 11,12 Türkiye'de ise bu oran %0,5-1,57 olarak bildirilmiştir. 13 Ülkemizde yapılan diğer çalışmalarda ise en düşük %0,72 oranında İç Anadolu Bölgesi'nde, en yüksek %2,97 oranında Karadeniz Bölgesi'nde tespit edilmiştir.…”
Section: Gereç Ve Yöntemunclassified
“…Çin'de yapılan bir çalışmada Liu ve ark. 11 en sık ilaçlar ile zehirlenmeleri bulurken bunu CO zehirlenmesi, besin zehirlenmesi ve pestisitlerin izlediğini tespit etmişlerdir. Ülkemizdeki çocuk zehirlenme olgularının değerlendirildiği çalışmalarda ilaçlar ile zehirlenmeler genellikle ilk sırada yer almaktadır.…”
Section: İstatistiksel Analizunclassified
“…Dünyanın birçok ülkesinde etiyolojik ve bireysel istatistikleri (7) 2010 yılında Katar'da yaptıkları bir çalışmada, acil servise zehirlenme nedeniyle başvuran hastalarda en sık neden olarak %61,6 oranında kimyasalların, ikinci sırada da %38,4 oranında ilaçların görüldüğünü bildirirken, Liu ve ark. 'nın (8) Çin'de yaptıkları çalışmada, sıklık sırasıyla; ilaçlar, CO zehirlenmesi, besin zehirlenmesi ve pestisitlerin görüldüğü rapor edilmiştir. Ülkemizde Ayoğlu ve ark.…”
Section: Discussionunclassified
“…In the study of Özayar et al (12), it was reported similarly that antidepressants were in the first order among drug intoxications with a rate of 31.9% and this was followed by analgesics with a rate of 17.02%. When the literature was examined, it was found that analgesics in some studies and antidepressants in some others were in the first order (15)(16)(17)(18)(19)(20)(21). In contrast to these studies, the rate of antibiotic intoxication was also found to be subtantially high in our study.…”
Section: Discussionmentioning
confidence: 99%